The Effects of Land Title Registration on Tenure Security, Investment and the Allocation of Productive Resources : Evidence from Ghana - Agyei-Holmes, Andrew (World Bank, Washington, DC, 2020)
Smallholder farmers' investment decisions and the efficiency of resource allocation depend on the security of land tenure. This paper develops a simple model that captures essential institutional features of rural land markets in Ghana, including the dependence of future rights over land on current cultivation and land rental decisions. The model predictions guide the evaluation of a pilot land titling intervention that took place in an urbanizing area located in the Central Region of Ghana. The evaluation is based on a regression discontinuity design combined with three rounds of household survey data collected over a period of six years. The analysis finds strong markers for the program's success in registering land in the targeted program area. However, land registration does not translate into agricultural investments or increased credit taking. Instead, treated households decrease their amount of agricultural labor, accompanied by only a small reduction of agricultural production and no changes in productivity. In line with this result, households decrease their landholdings amid a surge in land valuations. The analysis uncovers important within-household differences in how women and men respond differentially to the program. There appears to be a general shift to nonfarm economic activities, and women's business profits increased considerably.